2018
DOI: 10.1016/j.celrep.2018.03.113
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 Binding and Control of Chromosome-Internal DNA Replication Origins Is Limited by Telomere Sequestration

Abstract: The Saccharomyces cerevisiae telomere-binding protein Rif1 plays an evolutionarily conserved role in control of DNA replication timing by promoting PP1-dependent dephosphorylation of replication initiation factors. However, ScRif1 binding outside of telomeres has never been detected, and it has thus been unclear whether Rif1 acts directly on the replication origins that it controls. Here, we show that, in unperturbed yeast cells, Rif1 primarily regulates late-replicating origins within 100 kb of a telomere. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 31 publications
(77 reference statements)
7
46
0
Order By: Relevance
“…Deletion of RIF1 activates telomeric origin firing (Dave et al, 2014;Mattarocci et al, 2014;Peace et al, 2014;Hafner et al, 2018). This origin activation requires Rif1 binding to PP1 through canonical binding motifs RVxF and SILK, (Dave et al, 2014;Hiraga et al, 2014;Mattarocci et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of RIF1 activates telomeric origin firing (Dave et al, 2014;Mattarocci et al, 2014;Peace et al, 2014;Hafner et al, 2018). This origin activation requires Rif1 binding to PP1 through canonical binding motifs RVxF and SILK, (Dave et al, 2014;Hiraga et al, 2014;Mattarocci et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis across the entire Chromosome VI showed that the left telomeric origins also showed slight increase in activation in rif1∆ and rif1-pp1bs (Supplemental Figure 1E relating to Figure 1). To determine the extent of activation of each origin, we used a method similar to (Hafner et al, 2018) and compared the relative copy number at each origin in rif1∆ and rif1-pp1bs to WT. As expected, there was higher relative copy number at most origins in the rif1∆ and rif1-pp1bs mutants, with the majority of the change seen in typically late/inefficient origins, demonstrated by a low relative copy number in WT cells ( Figure 1D).…”
Section: Disruption Of Rif1 Binding To Pp1 Activates Origin Firingmentioning
confidence: 99%
“…In addition to subtelomeric origins, Rif1 regulates and associates with origins distal from telomeres and with the nuclear envelope, and therefore could potentially tether origins to the periphery (Fig. 7A) (Hafner et al, 2018;Park et al, 2011;Peace et al, 2014). Rif1's interacts with Dbf4 and with the counteracting PP1 phosphatase, suggesting that the Rif1--origin interaction may be down--regulated by DDK-dependent phosphorylation of MCM proteins and/or Rif1 (Dave et al, 2014;Hiraga et al, 2014;Mattarocci et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In budding and fission yeast, specific mechanisms defining replication timing are linked with chromosomal domain organization (reviewed in (Aparicio, 2013;Yamazaki et al, 2013). Rif1, which is highly enriched at telomeres, is globally responsible for delayed replication timing of subtelomeric domains as well as internal late--replicating domains (Hafner et al, 2018;Hayano et al, 2012;Peace et al, 2014;Tazumi et al, 2012). Rif1 acts by directly antagonizing replication initiation triggered by Dbf4--dependent kinase (DDK) phosphorylation of MCM helicase proteins (Dave et al, 2014;Hiraga et al, 2014;Mattarocci et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This scattered dispersion may explain why we have failed to detect IN1 and IN5 by ChIP-seq in these regions. High-resolution mapping of DNA binding sites will be required to address this point (Hafner et al, 2018;Meers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%